Identifying the tax compliance intention of SMEs in Cambodia: An analysis with the PLS-SEM - Eng, Ratana; Lim, Siphat (Edelweiss Applied Science and Technology, 2025)
The aim of this study was to identify the factors that influence behavioral intentions to comply with value added tax (VAT) in small and medium enterprises (SMEs) in Cambodia. Five latent variables such as attitude (ATT), patriotism (PAT), perceived behavioral control (PBC), subjective norms (SUN), and behavioral intention (BEI) to comply with VAT regulation, which was a dependent variable, were included in the Partial Least Square Structural Equation Modelling (PLS-SEM). After the two critical evaluations of the model—measurement model and structural model— two of the four independent variables—attitude and patriotism—were found to have a statistically significant positive influence on Cambodian SMEs' intention to comply with VAT regulation, at a 1% level for each coefficient. The f2 value of the two constructs was estimated to be 0.202 (ATT) and 0.242 (PAT). The R2 value was 0.914, which means that 91.4% of the variance in the BEI was explained by the independent variables, specifically ATT, PAT, PBC and SUN. The computed Q² value of 0.248 indicated that the model demonstrates a moderate degree of predictive relevance concerning the endogenous variables, implying that it had the capacity to explain roughly 24.8% of the variance present in the data.